Analisis Pengaruh EPS dan ROA terhadap Harga Saham Perusahaan yang terdaftar di Bursa Efek Indonesia - Diana; Khadijah (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
This study aims to provide empirical evidence about the analysis of the effect of EPS and ROA on stock prices of companies listed on the IDX. The population of this study amounted to 32 companies. The sample of this research is 9 companies listed on the IDX for the period 2016-2020. The method of determining the sample using purposive sampling method. The data used is secondary data collected using the nonparticipant observation method by downloading data from the IBM SPSS 25 website. The results of the partial study for EPS show a significance value of 0.000 < α = 0.05, which means that EPS has a significant influence on stock prices, this proves that the greater the fixed assets covering current liabilities does not cause the stock price to increase. The results of the partial study for ROA show a significance value of 0.228 > α = 0.05, which means that ROA has no significant effect on stock prices, which proves that companies that have high or low Return On Assets (ROA) do not necessarily have high or low stock prices. However, the results of simultaneous research, for the value of EPS and ROA showed a significance value of 0.000 < α = 0.05, which means that EPS and ROA have a significant effect on stock prices. For future research, it is better to add independent variables so that it can be known whether there are other variables that affect firm value.